WOMAN’S BRAVERY AGAINST GENDER INEQUALITY IN DANIELLE STEEL’S THE RIGHT TIME - Octavia Putri; Safitri Hariani (JOURNAL OF LANGUAGE, 2021)
This research is to  analyze  the bravery of a woman in facing gender inequality in Danielle Steel's Novel The Right Time. Alexandra Winslow is a young woman who has a dream to be a crime thriller story writer. During the journey of realizing her dream as a writer, she should be brave to face discrimination from male crime thriller writers and gender inequality from society. This research is completed by the use of descriptive qualitative method. The data are obtained by quoting related quotations from the story of the novel. Then, the data analysis is conducted by classifying the data related to the research problems of this study. The results show that there are three types of bravery done by the main character: bravery to fight against marginalization, abolish stereotype and thwart violence. Winslow's ability to write is not in doubt. Those who know Winslow closely and have read her writings find Winslow's writing to be extraordinary. Thanking to the support of the people around him, Winslow dares to continue her dream of becoming a famous writer even though she has to hide behind the identity of a man.